Communities perception of a proposed mine-mouth coal-fired power plant project in Benito Soliven, Isabela - Geges, D. B.; Amparo, J. S.; Jimena, C. G.; Mendoza, M. E. T.; Visco, E. S.; Comia, M. J.; Francisco, J. A.; Rutor, J. M. (2003)
This study was conducted to determine the communities perception on the proposed mine-mouth coal-fired power plant project in Barangay Dagupan and Villaluz, Benito Soliven, Isabela . Results showed that few (12%) from Dagupan and (9%) from Villaluz are unaware of the proposed project. Most (88%, Dagupan) and (91%, Villaluz) are aware to fully aware of the project. This is due to the information education communication campaign done by the PNOC-EC. With this awareness, majority (53%) in Dagupan and less than half (44%, 36%), environmental (47%, 31%), and resettlement (41%, 36%) in Villaluz and Dagupan, respectively. The communities negative perception may hinder the implementation of the project in future.
Keywords: Power plants